Ascorbic acid and its transporter SVCT2, affect radial glia cells differentiation in postnatal stages - Saldivia, Natalia; Salazar, Katterine; Cifuentes-Rueda, Manuel; Espinoza, Francisca; Harrison, Fiona E.; Nualart, Francisco (Wiley, 2024)
Radial glia (RG) cells generate neurons and glial cells that make up the cerebral cortex. Both in rodents and humans, these stem cells remain for a specific time after birth, named late radial glia (lRG). The knowledge of lRG and molecules that may be involved in their differentiation is based on very limited data. We analyzed whether ascorbic acid (AA) and its transporter SVCT2, are involved in lRG cells differentiation. We demonstrated that lRG cells are highly present between the first and fourth postnatal days. Anatomical characterization of lRG cells, revealed that lRG cells maintained their bipolar morphology and stem-like character. When lRG cells were labeled with adenovirus-eGFP at 1 postnatal day, we detected that some cells display an obvious migratory neuronal phenotype, suggesting that lRG cells continue generating neurons postnatally. Moreover, we demonstrated that SVCT2 was apically polarized in lRG cells. In vitro studies using the transgenic mice SVCT2+/− and SVCT2tg (SVCT2-overexpressing mouse), showed that decreased SVCT2 levels led to accelerated differentiation into astrocytes, whereas both AA treatment and elevated SVCT2 expression maintain the lRG cells in an undifferentiated state. In vivo overexpression of SVCT2 in lRG cells generated cells with a rounded morphology that were migratory and positive for proliferation and neuronal markers. We also examined mediators that can be involved in AA/SVCT2-modulated signaling pathways, determining that GSK3-β through AKT, mTORC2, and PDK1 is active in brains with high levels of SVCT2/AA. Our data provide new insights into the role of AA and SVCT2 in late RG cells.
Keywords: Vitamina C; Corteza cerebral; Células; Ascorbic acid; Cerebral cortex; Late radial glia; Neuronal differentiation; SVCT2; Vitamin C